Liquefaction resistance of sand reinforced with geosynthetics. Issue 5 (October 2008) - Altun, S.; Göktepe, A. B.; Lav, M. A.
Abstract : This paper describes an investigation into the performance of geosynthetics in enhancing the resistance to liquefaction of medium dense ( D r = 50%) sand deposits. Cyclic torsional shear tests were carried out on 99 laboratory test specimens under a confining pressure of 98 kPa and a loading frequency of 0.1 Hz. A series of shear stress ratios was used to evaluate the behaviour of sand under cyclic loading conditions. Different types of geotextile (woven, nonwoven) and different arrangements of geotextiles (one, two, three and four layers) were tested. Test results revealed that the liquefaction resistance of sand deposits can be significantly increased by geosynthetic reinforcement. Nonwoven geotextiles were found to perform better than woven geotextiles as reinforcement materials. The results indicate that both the type and the arrangement of reinforcements are crucial in increasing the liquefaction resistance of medium dense sands, and there can be significant variations in the behaviour, depending on the arrangement of the reinforcement.